Knowing, Doing, and Becoming Reflective Practitioners: A Narrative Inquiry of STEAM Educators - Sunar, Pushpa Kumari; Pant, Binod Prasad; Dahal, Niroj (Alberta Journal of Educational Research)

(untitled) (Faculty of Education, University of Alberta, 2024)
Reflective practice can guide educators toward enhancing their abilities, comprehension, and expertise, reflecting on their experiences to grow personally, professionally, and academically, thereby elevating the overall standard of their work. This paper aims to narrate the perception, practice, challenges, opportunities, and outcomes of reflective practices among STEAM (Science, Technology, Engineering, Arts, Math) educators in Nepal. Using narrative inquiry, we explored the reflective practice experiences of four STEAM educators, (three female and one male). Interview guidelines were used as a data collection tool to generate the participants' narratives. The guiding theoretical referents for this study were Dewey’s theory of experience and Mezirow’s transformative learning theory. The findings of this study show that STEAM educators perceived reflective practice as a tool to reflect on their actions, evaluate them, and learn from their experiences. Participants emphasized that teaching is a dynamic job with many challenges; however, reflective practices helped them realize their weaknesses and refine their efforts to create a better learning environment. It also enabled them to shift from traditional pedagogical practices to progressive ones, where learners were empowered through authentic and meaningful engagement in the learning process. Time management was seen as a significant challenge when practicing reflective practices; sometimes, the ego clash demotivated them to reflect on their actions. Despite challenges, participants also accepted that reflective practices allow them to explore and apply new ideas in their profession and transform their practices. Consequently, the perspectives offered in this paper may prove beneficial for other educators in cultivating reflective practitioners.